THE DEVONIAN TO PERMIAN SEDIMENTATION OF THE RUSSIAN PLATFORM: AN EXAMPLE OF SUBDUCTION-CONTROLLED LONG-WAVELENGTH TILTING OF CONTINENTS - Mitrovica J.X.; Pysklywec R.N.; Beaumont C.; Rutty A. (My University, 1996)
Stratigraphic evidence indicates that the Russian, or East European, Platform experienced two distinct episodes of long-wavelength down to the east tilting during the Devonian to Permian period. We demonstrate a correlation between these tilting events and two separate periods of inferred west-dipping subduction under the platform (active between 400-340 Ma and 311-290 Ma). These subduction events consumed the ancient Uralian Ocean and ended with the onset of Uralian orogeny. We propose that the platform tilting episodes were due to the dynamic response of the Euramerican plate to mantle flow viscously coupled to these contemporaneous subduction events. We present numerical simulations of mantle convection driven by descending viscous slabs which are able to reconcile the thickness of the sediment deposition, the maximum horizontal wavelength of the tilt, and the onlap/offlap (sea level transgression/regression) sequence for each tilting event on the platform. These simulations also require high plate convergence rates during active subduction which are consistent with the geological record.
Keywords: Permian; Devonian; Палеозой::Пермская; Paleozoic::Devonian; Paleozoic::Permian; Палеозой::Девонская